(untitled) (Research, Society and Development, 2020)
The state of Pará has experienced a high occurrence of forest fires, which were strongly influenced by the El Niño phenomenon in 2015-2016. This study aims to analyze the conditions of heat sources in Pará, using the 2016 monthly bulletins provided by the Environment and Sustainability Secretariat. This data was analyzed through descriptive statistics. The IDW interpolation method was used to construct the density map, displaying the primary areas of concern. The results showed that the greatest detections were during the Amazonian summer, occurring during the second half of the year. Specifically, the municipalities of the Southwestern and Southeastern Para meso-regions were mainly the ones affected. Fire is used as a primary economic tool. The Southwest was the one region that presented the highest densities of hotspots. Although the results do not indicate the actual configuration of the events, because of the technical limitations of remote sensing, the information obtained in this study communicates ideas concerning prevention and action in the most affected areas. In loco studies are needed to determine precisely the causes of these occurrences.